Do firm, governance, and country characteristics predict financial constraints across GCC stock markets? - Tamer Elshandidy; Hashem Eldash; Nehal Allam (Cogent Business & Management)
The paper explores the extent to which firm-level characteristics, governance attributes, and country-level characteristics predict the financial constraints of non-financial listed firms in stock markets for countries in the Gulf Corporation Council (GCC). The study employs widely used explanatory indicators in the less studied context of GCC to capture three significant effects of firm-specific, governance mechanisms, and country-specific characteristics used for predicting financial constraints. Across seven different GCC stock markets, financial data were collected from 2010 to 2020, resulting in having 2211 firm-year observations. Our multivariant analysis shows that combining indicators to capture firm-specific, governance, and country-specific attributes improved the ability of the empirical model to predict the financial constraints for non-financial firms in the GCC. These empirical findings statistically specify the significant indicators at each level of explanatory variables. The empirical results further indicate that an Altman Z-score is a better indicator than the Current Ratio as a responding variable to predict financial constraints in the GCC stock markets. Overall, the paper’s results are essential for investors and market regulators in the GCC and other contexts since firms’ financial constraints are one of the most prominent aspects that threaten the continuity of these firms.